Shrewd vehicle framework model with a streamlined informed approach for green transportation in smart cities - Tao, Hai; Wang, Jing; Yaseen, Zaher Mundher; Mohammed, Muamer N.; Jasni, Mohamad Zain (Elsevier Inc., 2021)
Infrastructure is essential for the activity of a smart city in lighting framework, water conveyance system, smart monitoring infrastructure, and so on. Presently the transport framework is set at the task of such smart city by making smooth portability of the individuals and products, particularly with the probability of managing traffic clog, giving up-dated information and in time data from the open transportation client, creating green methods for transportation (bicycle and vehicle sharing for example), and so on. This paper is highly engaged in keeping up the shrewd vehicle framework model with a streamlined informed approach, which has been planned and created depending on the Smart City segment. This smart model vehicle framework has added to the structure and planning for a smart city by making it increasingly important with a superior utilization of offices, less noisy, free of accidents, progressively conscious of condition with web organized analysis for utilizing data from the clients for adjusting the transportation administrations. Further, the ability to serve the client by giving it to them with open transportation and increasingly interconnected stations moves towards urban areas inside the city.